Littératie algorithmique et pratiques médiatiques des jeunes à Bruxelles - Sylvain Malcorps; Arnaud Claes; Thibault Philippette; Marie Dufrasne (Brussels Studies)
Recommendation algorithms play an undeniable role in the access to information, and are aimed at making browsing easier for users by recommending the most "relevant" content according to a series of criteria selected by their designers. At the same time, these mechanisms participate in the economic functioning of these platforms by helping to capture and retain the attention of the users of these services. It is therefore crucial to have a better understanding of the social issues raised by these technologies. To the extent that young people in Brussels receive their information mainly via social networks, the ALG-OPINION project focused on the way in which they perceive the functioning of these technologies and on the media practices they develop due to their experiences with them. By focusing on the specific practices of young users in Brussels, the work presented in this article provides a more detailed interpretation of the actual relationships these audiences have with the algorithmic technologies they encounter on a daily basis. This article concludes with an exploration of media education approaches which take these observations into account.